A combination of silica and cigarette smoke extract exacerbates lung fibrosis: Unveiling a harmful synergy - Fahad Alsohime; Narjes Saheb Sharif-Askari; Nasser Saleh Alharbi; Mohammed Faraj Ayad Alosaimi; Rabih Halwani (PLoS ONE, 2025)
Smoking could potentiate the profibrotic effects of silica in the lungs, including increasing the risk of cancer and silicosis. Crystalline silica-induced silicosis has been associated with lung fibrosis. Moreover, smoking is strongly linked with an increased risk of idiopathic pulmonary fibrosis. Although pulmonary fibrosis is a recognized feature in asthma airway modeling, the effects of cigarette smoke and silica, both individually and together, have not been studied. We examined the effect of cigarette smoke extract (CSE) on silica-induced fibrosis in asthmatic patients and healthy individuals by using fibroblasts from both groups. Cigarette smoke enhanced the fibrotic effects of silica in healthy and asthmatic lung fibroblasts. Healthy fibroblasts exhibited low baseline levels of fibrotic proteins. However, exposure to CSE and silica significantly increased extracellular matrix (ECM) markers. Asthmatic fibroblasts, with higher baseline levels of these markers, showed even greater upregulation upon exposure. The combination of silica and cigarette smoke also promoted collagen deposition and upregulated levels of matrix metalloproteinases (MMPs) and their inhibitors (TIMP-1 and TIMP-2) in asthmatic fibroblasts. Cessation of smoking and control of silica exposure are essential for reducing lung inflammation and fibrosis. Additionally, therapeutic targets should be investigated for their protective effects against these toxins.